Nanoemulsions: stability and physical properties - Montes de Oca Avalos, Juan Manuel (2017)
Nanoemulsions present several advantages over conventionalemulsions due to the small droplets size they contain: highoptical clarity, good physical stability against gravitationalseparation and droplet aggregation, and enhancedbioavailability of encapsulated substances, which make themsuitable for food applications. Depending on desiredformulation, preparation method should be selected tooptimize droplet size distribution since it strongly affectsstability behavior. Systems with droplets diameter smaller than200 nm and a monomodal distribution usually have ahomogeneous structure, that is, a structure with well-distributed droplets that do not show flocs. A structure withthese characteristics remains unchanged for long time, up tosix months, given the nanoemulsion enhanced stabilitycompared to conventional emulsions with the sameformulation.